Dual role of nitrergic neurotransmission in the bed nucleus of the stria terminalis in controlling cardiovascular responses to emotional stress in rats - Barretto-de-Souza, Lucas [UNESP]; Adami, Mariane B [UNESP]; Benini, Ricardo [UNESP]; Crestani, Carlos C [UNESP] (Wiley, 2018)
Background and Purpose: The aim of the present study was to assess the interaction of nitrergic neurotransmission within the bed nucleus of the stria terminalis (BNST) with local glutamatergic and noradrenergic neurotransmission in the control of cardiovascular responses to acute restraint stress in rats. Experimental Approach: Interaction with local noradrenergic neurotransmission was evaluated using local pretreatment with the selective α1-adrenoceptor antagonist WB4101 before microinjection of the NO donor NOC-9 into the BNST. Interaction with glutamatergic neurotransmission was assessed by pretreating the BNST with a selective inhibitor of neuronal NOS (nNOS), Nω-propyl-L-arginine (NPLA) before local microinjection of NMDA. The effect of intra-BNST NPLA microinjection in animals locally pretreated with WB4101 was also evaluated. Key Results: NOC-9 reduced the heart rate (HR) and blood pressure increases evoked by restraint stress. These effects of NOC-9 on HR, but not in blood pressure, was inhibited by pretreatment of BNST with WB4101. NMDA enhanced the restraint-evoked HR increase, and this effect was abolished following BNST pretreatment with NPLA. Administration of NPLA to the BNST of animals pretreated locally with WB4101 decreased the HR and blood pressure increases induced by restraint. Conclusion and Implications: These results indicate that inhibitory control of stress-evoked cardiovascular responses by nitrergic signalling in the BNST is mediated by a facilitation of local noradrenergic neurotransmission. The present data also provide evidence of an involvement of local nNOS in facilitatory control of tachycardia during stress by NMDA receptors within the BNST.